2021
DOI: 10.3390/plants10122618
|View full text |Cite
|
Sign up to set email alerts
|

Yield and In Vitro Antioxidant Potential of Essential Oil from Aerva javanica (Burm. f.) Juss. ex Schul. Flower with Special Emphasis on Seasonal Changes

Abstract: The essential oil (EO) of the desert cotton (Aerva javanica (Burm. f.) Juss. ex Schul.) was extracted by hydrodistillation, from A. javanica flowers growing in the sandy soils of the United Arab Emirates (UAE) wild desert. The influence of seasonal variation on flowers’ EO yield was studied. The flowers’ EO yield obtained from spring samples (0.011%) was significantly the highest followed by early summer (0.009%), winter (0.007%), and autumn samples (0.006%), respectively. The flowers’ EO antioxidant analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The results obtained explicated that the terpenoids are the main constituents of both plants, with a relative concentration of 93.59% and 97.66%, respectively, mainly including sesquiterpenes (93.40% and 81.06%) [ 11 ]. Another study conducted by Shahin et al [ 12 ] reported that the flowers’ EO extracted from Aerva javanica , isolated during four seasons, is considered a good source of natural bioactive antioxidants. Khalil et al [ 13 ] studied the chemical composition of EO isolated from Anisosciadium lanatum and evaluated its anti-cancer potential and mechanistic effect on HepG2 liver cancer cell lines.…”
Section: Bio-pharmaceutical Propertiesmentioning
confidence: 99%
“…The results obtained explicated that the terpenoids are the main constituents of both plants, with a relative concentration of 93.59% and 97.66%, respectively, mainly including sesquiterpenes (93.40% and 81.06%) [ 11 ]. Another study conducted by Shahin et al [ 12 ] reported that the flowers’ EO extracted from Aerva javanica , isolated during four seasons, is considered a good source of natural bioactive antioxidants. Khalil et al [ 13 ] studied the chemical composition of EO isolated from Anisosciadium lanatum and evaluated its anti-cancer potential and mechanistic effect on HepG2 liver cancer cell lines.…”
Section: Bio-pharmaceutical Propertiesmentioning
confidence: 99%
“…In Pakistan, it thrives well on calcareous and sandy soils of arid and semiarid rangelands. In English, it has different names like Aerva, Java Aerva, Kapok bush, Snow bush and Pillow bush (Ruffo et al2002;Shahin et al 2021). This perennial shrub grows to a medium height.…”
mentioning
confidence: 99%
“…e studies reported by Bouksaim et al [27], Ismail et al [28], and Shahin et al [29] show a high yield from the cones compared to that from the leaves, which is in accordance with the results of our study. However, the difference in the EO yield in aromatic and medicinal plants can be explained by several parameters such as season [30], geographical origin [31], and the part of the treated plant [28].…”
Section: Essential Oil Yieldmentioning
confidence: 99%